Pandemic democracy: the nexus of covid-19, shrinking civic space for civil society organizations and the 2020 elections in Ghana. Issue 5 (4th July 2022) - Kumi, Emmanuel
ABSTRACT: In Ghana, civil society organizations (CSOs) play significant roles in promoting democratic development. However, the space within which they operate is increasingly becoming restricted. Coupled with this, COVID-19 inspired legislations are disrupting civil society, increasing existing threats to civic space, and creating uncertainties for Ghana's 2020 elections. Yet, our understanding of how the COVID-19 pandemic influences civic space and elections remains limited. Drawing on media reviews and 22 semi-structured interviews with CSO representatives and key informants, we find that the pandemic poses threats to civic space in terms of curtailment of freedoms of expression, movement and peaceful assembly. We also demonstrate that while the COVID-19 pandemic created uncertainties with the processes leading to the 2020 general elections, it had minimal effects on the elections due in part to the proactiveness and preparedness of the Electoral Commission in election administration. Notwithstanding, our findings show that the pandemic heightened and created opportunities for promoting polarized online campaigns characterized by hate speech and the propagation of fake news as political parties resorted to the use of social media in reaching out to voters. This undermines efforts for promoting democratic development and open civic space. Implications of the research findings are discussed.